2020
DOI: 10.1292/jvms.19-0452
|View full text |Cite
|
Sign up to set email alerts
|

Effects of several organophosphates on hepatic cytochrome P450 activities in rats

Abstract: Four commonly used organophosphates (fenitrothion, dichlorvos, chlorpyrifos, and trichlorfon) were orally administered to male Sprague-Dawley rats for five days in order to explore their effects on the activities of liver cytochrome P450 (CYP). In addition, Michaelis-Menten kinetics of the metabolic reactions catalyzed by liver CYPs were analyzed following the addition of these compounds to the assay system to examine their potential inhibitory effects on liver CYPs activities. These reactions included ethoxyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…On the other hand, as DCV is an oxon compound and is not subjected to oxidative desulfuration in the liver, this compound exhibited low inhibition potency against all oxidative activities tested (see Figures 1a-e and Table 2). This fact is in agreement with previous observations on the low or negligible inhibitory effects of this OP compound against CYP-dependent metabolic reactions in rats (Abdou et al, 2020).…”
Section: F I G U R Esupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, as DCV is an oxon compound and is not subjected to oxidative desulfuration in the liver, this compound exhibited low inhibition potency against all oxidative activities tested (see Figures 1a-e and Table 2). This fact is in agreement with previous observations on the low or negligible inhibitory effects of this OP compound against CYP-dependent metabolic reactions in rats (Abdou et al, 2020).…”
Section: F I G U R Esupporting
confidence: 93%
“…It has been suggested that CYP inhibition by OPs containing a phosphorothionate group is a consequence of the release of reactive sulphur during this oxidative desulfuration (Butler & Murray, 1997; Hodgson & Rose, 2007). Thus, inhibition of different CYPs, including those involved in their metabolism, has been widely described, at least in rats (Abdou et al, 2020) and humans (Abass et al, 2009; Abass & Pelkonen, 2013; Hodgson & Rose, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pesticides are used widely to promote crop yield and eradicate pests (Abdou et al, 2020). Unfortunately, their environmental levels are a global issue of concern (Taiwo, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The liver is the most responsible organ for the detoxification and removal of toxic chemicals, xenobiotics, and different medications (Abdou et al 2020; Soliman et al 2022a,b). Because of this, even at therapeutic levels, any drug might have an adverse effect on the liver (Osterreicher and Trauner, 2012).…”
Section: Introductionmentioning
confidence: 99%